Enteric-coated Mycophenolate Sodium therApy versus cyclophosphamide for induction of Remission in Microscopic PolyAngiitis (EMSAR-MPA trial): study protocol for a randomised controlled trial - Lihua Wang; Sijia Li; Xiaojing Shi; Xiaole Su; Shulei Yao; Xuan Tie; Rongrong Feng (BMJ Open, 2024)
Introduction Several studies have demonstrated that mycophenolate mofetil (MMF) may be an excellent alternative to cyclophosphamide (CYC) or rituximab for the induction of remission in non-life-threatening anti-neutrophil cytoplasmic antibodies associated vasculitis because of its strong immunosuppressive potency and low toxicity profile. Enteric-coated mycophenolate sodium (EC-MPS) was introduced to reduce gastrointestinal adverse reactions of MMF. This study will evaluate the efficacy and safety of EC-MPS combined with glucocorticoid in patients with active and non-life-threatening microscopic polyangiitis (MPA).Methods and analysis This study is a multicentre, open-label, randomised controlled, non-inferiority trial. A total of 110 patients with active and non-life-threatening MPA from 11 hospitals in Shanxi Province of China will be recruited and randomised in a 1:1 ratio to receive either EC-MPS or CYC. All patients will receive the same glucocorticoid plan. We will compare oral EC-MPS (720–1440 mg/day) with intravenous pulsed CYC (7.5–15 mg/kg) administered for 3–6 months. All patients will be switched from their assigned treatment (EC-MPS or CYC) to oral azathioprine (2 mg/kg/day) after remission has been achieved, between 3 and 6 months. Azathioprine will be continued until the study ends at 18 months. The primary end point of efficacy is the remission rate at 6 months. Follow-up will continue for 18 months in order to detect an influence of induction regimen on subsequent relapse rates.Ethics and dissemination This study has received approval from the Ethics Committee of the Second Hospital of Shanxi Medical University (2022YX-026). All participants are required to provide written informed consent and no study-related procedures will be performed until consent is obtained. The results of this trial will be published in peer-reviewed journals and presented at conferences.Trial registration number ChiCTR2200063823.